2022
DOI: 10.3390/nu14204297
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Concepts on Inflammatory Biomarkers and Malnutrition in Chronic Kidney Disease

Abstract: While patient care, kidney replacement therapy, and transplantation techniques for chronic kidney disease (CKD) have continued to progress, the incidence of malnutrition disorders in CKD appears to have remained unchanged over time. However, there is now a better understanding of the underlying pathophysiology according to the disease background, disease stage, and the treatment received. In CKD patients, the increased production of proinflammatory cytokines and oxidative stress lead to a proinflammatory milie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 67 publications
0
32
0
1
Order By: Relevance
“…In respect to evaluation of the nutritional status in clinical practice, there are different methods that can be used in order to infer about body composition of chronic kidney patients under dialysis treatment [15]. BIA has been validated in this population, and phase angle (PhA) is a derived variable that indicates alterations in cell membrane and intercelular space integrity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect to evaluation of the nutritional status in clinical practice, there are different methods that can be used in order to infer about body composition of chronic kidney patients under dialysis treatment [15]. BIA has been validated in this population, and phase angle (PhA) is a derived variable that indicates alterations in cell membrane and intercelular space integrity [16].…”
Section: Discussionmentioning
confidence: 99%
“…There are diverse scores and tools to assess nutritional status, although there are no current strong recommendations. Besides clinical scales, we usually employ bioelectrical impedance analysis (BIA), a rapid, fairly cheap and non-invasive method, whose evaluation consists of a body passage of an electric current, wich gives us information about body composition and nutritional status [14][15][16][17]. By using BIA it is possible to obtain the phase angle value (PhA), which is the resistance/ reactance ratio of body tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the presence of malnutrition-inflammation-cachexia syndrome in these patients with chronic kidney disease, but multiple mechanisms are likely to be involved. Increases in the concentrations of pro-inflammatory cytokines can induce anorexia, which is accompanied by chronic fatigue and the breakdown of muscle proteins, ultimately leading to a reduction in nutrient intake, greater resting energy expenditure, and muscle atrophy (31,32). Patients with low LCR are more likely to develop malnutrition-inflammation-cachexia syndrome, involving low circulating creatinine, urea, and albumin concentrations.…”
Section: B Amentioning
confidence: 99%
“…Chronic in ammation leads to protein energy wasting (PEW) and is associated with poor cardiovascular outcomes. [3][4][5] Investigating any treatable cause of in ammation in PD patients with persistently elevated C-reactive protein and continuously monitoring nutritional status to identify PD patients with PEW has become one of the key measures to reduce cardiovascular risk. [6] The advanced lung cancer in ammation index (ALI) which is based on albumin, body mass index, and neutrophils to lymphocytes ratio, was rst developed by Jafri et al and has been shown to be a novel in ammatory parameter for predicting prognosis in metastatic non-small cell lung cancer [7].…”
Section: Introductionmentioning
confidence: 99%